2019
DOI: 10.3390/ijerph16030346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-Week Swimming Training on Body Composition in Young Women

Abstract: Background: Systematic physical activity can permanently prevent disadvantageous developments in the human body. This is very important especially for women, for whom the maintenance of a lean body in good shape is sometimes a primary consideration. However, in most cases, this activity is taken randomly and does not produce the desired effects such as reducing body fat. The purpose of the study was to evaluate changes in female body composition induced by 12 weeks of swimming training compared to sedentary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
19
0
3
Order By: Relevance
“…Siqueira et al (2017) found no changes in the body composition of women with rheumatoid arthritis who participated in 16 weeks supervised programme comprising various types of water exercise in the form of three weekly sessions. Charmas et al (2019) carried out swimming training, which lasted twelve weeks with three-time per week, in young women; mo changes were found in body weight and FM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siqueira et al (2017) found no changes in the body composition of women with rheumatoid arthritis who participated in 16 weeks supervised programme comprising various types of water exercise in the form of three weekly sessions. Charmas et al (2019) carried out swimming training, which lasted twelve weeks with three-time per week, in young women; mo changes were found in body weight and FM.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, literature reviews confirm the usage of aquatic exercise to promote body weight and composition (Penaforte et al, 2015;Pereira et al, 2018;Rezaeipour & Apanasenko, 2019). Other researchers do not accept the effect of water exercises on body weight (Charmas & Gromisz, 2019) and composition (Charmas & Gromisz, 2019;Rica et al, 2013;Siqueira et al, 2017), and there is still controversy over this issue (Rezaeipour, 2020). Also, no literature has been found that would specifically assess the efficacy of the WATERin-MOTION aquatic exercise programme on body weight and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high-intensity interval training was effective on reduced caspase-9 levels in the heart tissue of rats with myocardial infarction (12). It seems that the type of training and training physiology in different settings have different effects on the physiology of the body, as the study by Charmas and Gromisz stated that swimming training had a significant effect on the improvement of physical composition (13). In addition, sports exercises along with crocin and saffron consumption had significant effects on the improvement of apoptosis in the cardiac tissue (10) and pancreas (14) and improved the sugar and metabolism parameters (15) in rats with type 1 and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, literature studies support aqua training to promote body composition variables (12)(13)(14). Some other researchers have not acknowledged the impact of aqua training on human body composition (15)(16)(17), and still, there are disagreements regarding the effect of aqua training on body composition variables (11). The WATERinMOTION (WiM) delivers a highenergy, low-impact exercise for any ages, skills, and fitness levels.…”
Section: Introductionmentioning
confidence: 99%